HUBUNGAN PREEKLAMPSIA BERAT DENGAN KOMPLIKASI PADA JANIN DI RSUD ABDUL 2 WAHAB SJAHRANIE SAMARINDA 3 TAHUN 2017-2018 - Rifqiya Faiza, Mita Maulida; Fransiska Ngo, Novia; Fikriah, Ika (Sekolah Tinggi Ilmu Kesehatan Mutiara Mahakam, 2019)
Preeclampsia defined as new onset of hypertension and proteinuria after 20 weeks of gestation. Preeclampsia is one of the three main causes of maternal mortality with an incidence of 128,273 each year or around 5.3% in Indonesia. Preeclampsia is classified as preeclampsia without severe features and severe preeclampsia. Severe preeclampsia can be a problem, both in the mother and the fetus due to vascular vasospasm. If uteroplacental blood flow to the fetus is limited, the fetus can be born under low birth weight (LBW), preterm birth, intra uterine fetal death, and low Apgar score. The aim of this research is to determine the correlation of severe preeclampsia with fetal complication, that is intra uterine fetal death (IUFD), preterm labor, neonatal asphyxia, and low birth weight (LBW). The design of this research is case control study with 46 sample for both case and control groups. The data analysis used chi-square for 2x2 table and likelihood ratio for 2x3 table. The results of this this research is showed that there was correlation between severe preeclampsia with preterm labor (p=0,000)and severe preeclampsia with low birth weight (p=0,000), there was no correlation between severe preeclampsia with IUFD (p=0,822) and severe preeclampsia with neonatal asphyxia (p=0,060)